If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 3c + 1 Reorder the terms: 10 = 1 + 3c Solving 10 = 1 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 10 + -3c = 1 + 3c + -3c Combine like terms: 3c + -3c = 0 10 + -3c = 1 + 0 10 + -3c = 1 Add '-10' to each side of the equation. 10 + -10 + -3c = 1 + -10 Combine like terms: 10 + -10 = 0 0 + -3c = 1 + -10 -3c = 1 + -10 Combine like terms: 1 + -10 = -9 -3c = -9 Divide each side by '-3'. c = 3 Simplifying c = 3
| 4x-9y=-68 | | 2s+4=10 | | -10+.25t=5 | | -10+.25t=-5 | | 9-2u=3 | | 4x+12-8x=24-6x | | 7a^2+80a+100=0 | | x^2+3x-18=9x-2 | | 1+(x+4)=8 | | 70=-7(-2--2) | | 7x+4y=34 | | 59-19=5(x-1) | | x^2-7x+14=4 | | 7x+4ty=34 | | 5b^2+9b+3=-2-9b^2 | | 34+4y-10=14y-12-4y | | 14=7-4x-32 | | x^2+3x-5x-15=0 | | 11=4-w | | y=x^2-5x-4 | | (2n+5)(n-4)=0 | | 20mn-15n= | | x+3=2x-6+5x | | x^2-53x+2y=0 | | (2424)-(4435)= | | 20x^6y+40x^4y^2-10x^5y^5= | | 45x^2+8=-26x | | -12=-3+14(2X+3) | | 6x^2-2x+8=0 | | 4x+7=15+3c | | 5(x-1)=2 | | 50-25x-2=10x+10 |